Emerging Roles of Long Non-Coding RNAs in Ankylosing Spondylitis - Sun, Ruifu; Wang, Xuesong; Sun, Xiaohong; Zhao, Bing; Zhang, Xiugong; Gong, Xiaojin; Wong, Sunny Hei; Chan, Matthew Tak Vai; Wu, William Ka Kei (Frontiers in Immunology, 2022)
Ankylosing spondylitis (AS) is a chronic systemic autoimmune disease characterized by inflammation, bone erosion, spur formation of the spine and the sacroiliac joints. However, the etiology and molecular pathogenesis of AS remain largely unclear. Recently, a growing number of studies showed that long non-coding RNAs (lncRNAs) played critical roles in the development and progression of autoimmune and orthopedic conditions, including AS. Studies demonstrated that a myriad of lncRNAs (e.g. H19, MEG3, LOC645166) pertinent to regulation of inflammatory signals were deregulated in AS. A number of lncRNAs might also serve as new biomarkers for the diagnosis and predicting the outcomes of AS. In this review, we summarize lncRNA profiling studies on AS and the functional roles and mechanism of key lncRNAs relevant to AS pathogenesis. We also discuss their potential values as biomarkers and druggable targets for this potentially disabling condition.